The epibiotic relationship between mussels and barnacles - Bell, Caroline Margaret (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2014)
Epibiosis is an ecological relationship that has been described as one of the closest possible associations in marine ecosystems. In the space limited rocky intertidal, mussel beds provide important secondary space for barnacles. The epibiotic relationship between mussels and barnacles on the south-east coast of South Africa was considered at different scales, from large-scale, natural patterns of epibiosis on the rocky shore, to fine-scale settlement choices of barnacles and the effects on the condition and growth rates of individual mussels. Mussel and barnacle assemblages were generally stable over a 12-month period. The tracking of individual mussels with and without barnacle epibionts resulted in a significant increase in mortality rate of mussels with epibionts over 12 months (two-way ANOVA, p = 0.028). Barnacles on rocks, as well as on mussels, were also tracked with no significant effect of substratum on mortality of barnacles (two-way ANOVA, p = 0.119). Prevalence and intensity of barnacle infestations was also examined in relation to coastline topography on two co-occurring mussel species, the indigenous Perna perna and invasive Mytilus galloprovincialis. The results were complex, but bay status had significant effects on prevalence and intensity for both mussel species, depending on the time and zone. The effect of bay in relation to time was particularly relevant for M. galloprovincialis (four-way nested ANOVA, Season X Site(Bay): p = 0.0002), where summer prevalence was higher than that of winter in bays, regardless of zone, while in open coast sites, the effect of season was only significant in the mid zone. Patterns of intensity generally showed higher values in summer. Substratum preference by barnacles was investigated by recording settlement, survival and mortality of Chthamalus dentatus barnacles on various treatments. There was a strong preference for the rock-like plastic substratum by primary settlers (pair-wise tests of PERMANOVA: Dead < Rock mimic (p = 0.0001); Replica < Rock mimic (p = 0.019) and Live < Rock mimic (p = 0.0001)). This indicates that barnacles settle on mussel shells only as a secondary choice and that micro-topography is an important variable in barnacle settlement. The effect of barnacle epibiosis on condition index and growth of P. perna and M. galloprovincialis was also examined as a direct indication of the health of mussels subjected to the biological stress of epibiosis. Although not significant (PERMANOVA: P. perna: p(perm) = 0.890; M. galloprovincialis: p(perm) = 0.395), growth for both mussel species was slower for barnacle-infested individuals in summer, which is the main growing season for mussels in the region. Results from condition index calculations, however, showed no negative impacts of epibiotic barnacles (three-way ANCOVA: P. perna: p = 0.372; M. galloprovincialis: p = 0.762). Barnacle epibionts create a new interface between the mussel and its environment and this interaction can affect other members of the community. The possibility of the barnacle epibiont causing increased drag also needs further investigation. Biological processes operating within a wide range of physical stressors drive the interactions on the rocky shore, such as epibiosis. Overall, the results of this study suggest that the epibiotic relationship between mussels and barnacles on the south-east coast of South Africa does not significantly affect the mussel species present and that barnacles only use mussel shells as a secondary choice of substratum.
Keywords: Epibiosis; Mussels -- Ecology -- South Africa; Mussels -- Behavior -- South Africa; Mussels -- Habitat -- South Africa; Barnacles -- Ecology -- South Africa; Barnacles -- Behavior -- South Africa; Barnacles -- Habitat -- South Africa; Perna -- Behavior -- South Africa; Mytilus galloprovincialis -- Behavior -- South Africa; Marine biodiversity -- South Africa